Analisis Kesalahan Morfologi pada Berita Online Surat Kabar Republika - Dwi Yuningsih; Kembong Daeng; Andi Fatimah Yunus (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the forms of morphological errors in the form of affixation, reduplication, and composition in online news articles published in the Republika newspaper from January to April 2025. This is a qualitative study using descriptive analysis techniques and a hermeneutic approach. The data collection technique used was documentation with the read, note, and conclude method. Data analysis was carried out through the stages of identification, classification, analysis, interpretation, and drawing conclusions based on morphological theory and error indicators from Setyawati (2019). The results show that morphological errors include the omission or inappropriate use of affixes, reduplication errors in the form of omitted hyphens, and inaccuracies in writing compound words. These findings indicate that morphological errors in Republika online news articles are relatively minimal, likely due to the editing process and the characteristics of journalistic language. However, the inaccuracies that are still found have the potential to affect the clarity of meaning and sentence structure.